1997
DOI: 10.1002/aic.690430106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cake growth in cake filtration: Effect of fine particle retention

Abstract: Equations were derived that describe the dynamics of cake growth in cake filtration, and methods for their solutions were developed. In deriving the equations, the moving boundary nature of the cake formation process and the effect of fine particle retention were considered. It was shown that fine particle retention may contribute significant4 to the decrease of cake permeability and thus alters the petjiormance of cake filtration even if the amount of fine particles involved is small. Through numerical exampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
88
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 6 publications
2
88
0
Order By: Relevance
“…When the drilling fluid contains particles of different sizes, the larger particles of the drilling fluid form the skeleton of the filter cake and the smaller particles can migrate and deposit within the porous cake formed by the large particles. Simultaneously, the cake may undergo a compaction process by the effect of the fluid drag as the suspension of smaller particles flow through the cake [5]. Polymer additives are capable of intercalating a large amount of water with their stretch of long chains.…”
Section: Introductionmentioning
confidence: 99%
“…When the drilling fluid contains particles of different sizes, the larger particles of the drilling fluid form the skeleton of the filter cake and the smaller particles can migrate and deposit within the porous cake formed by the large particles. Simultaneously, the cake may undergo a compaction process by the effect of the fluid drag as the suspension of smaller particles flow through the cake [5]. Polymer additives are capable of intercalating a large amount of water with their stretch of long chains.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, considering a constant concentration of the feed and given a cake capturing practically all particles, it can be observed that the cake thickness grows slower than linearly while the pressure drop curve exhibits a superlinear behavior. One explanation is the compaction of the cake due to pressureinduced mechanical compression [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The incompressible filter cake is completely built by the filter-aid, which allows describing an evolution equation based on the mass balance of filter-aid at the surface. Models for compressible filter cake were developed in [5][6][7]. There, the small particles can penetrate the cake layer, but all the larger particles are completely deposited at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…When the drilling fluid contains particles of different sizes, the larger particles of the drilling fluid form the skeleton of the filter cake and the smaller particles can migrate and deposit within the porous cake formed by the large particles. Simultaneously, the cake may undergo a compaction process by the effect of the fluid drag as the suspension of smaller particles flow through the cake [4]. The particle size distribution (PSD) of solids in the filter cake is determined using a conventional laser light scattering instrument [5] and using a laser diffraction method [6].…”
Section: Introductionmentioning
confidence: 99%